"It Started With This Project": A Mixed Methods Examination of a Service Learning Project for Preservice Art Educators. (1st October 2020) - Alexander, Amanda S.; Murphy, Erin Roark
Abstract : The objective of this study is to better understand preservice art educators' experiences engaging in a service learning project. The study uses a mixed methods, longitudinal design with data collected through student pre- and posttest surveys and written reflections over 7 years. Findings indicate three themes that describe preservice art educators' experience of participating in service learning: (1) skill development ; (2) breaking down barriers, challenging stereotypes, and building relationships ; and (3) plans for future teaching and civic engagement . The qualitative findings lend support to the quantitative findings of improved learning outcomes (e.g., active learning skills, clearer idea of personal goals, more concern about social phenomena, better understanding of stereotypes, and increased likelihood of participation in future civic and volunteer activities) and provide insight into the nuances of student experiences, ultimately leading to recommendations and considerations for future service learning project design.